Angle of Incidence Effects in Reflectarray Antenna Design: Making gain increases possible by including incidence angle effects - Almajali, E'qab R.F.; McNamara, Derek A. (IEEE antennas & propagation magazine, 2016)
The subject of whether or not it is necessary to include a feed field incidence angle in the design of main reflectarrays and subreflectarrays is discussed quantitatively in this article. The performance of reflectarray designs done with and without such incidence angle effects included are compared. The additional gain is achieved if the incidence angle is indeed included in the design process. The immunity of subwavelength elements to incidence angle effects is confirmed and illustrated using individual element patterns. Subreflectarrays designed with such subwavelength elements are shown to exhibit superior performance compared to those using half-wavelength ones.